2012
DOI: 10.1021/ml300110s
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of CX-5461, the First Direct and Selective Inhibitor of RNA Polymerase I, for Cancer Therapeutics

Abstract: Accelerated proliferation of solid tumor and hematologic cancer cells is linked to accelerated transcription of rDNA by the RNA polymerase I (Pol I) enzyme to produce elevated levels of rRNA (rRNA). Indeed, upregulation of Pol I, frequently caused by mutational alterations among tumor suppressors and oncogenes, is required for maintenance of the cancer phenotype and forms the basis for seeking selective inhibitors of Pol I as anticancer therapeutics. 2-(4-Methyl-[1,4]diazepan-1-yl)-5-oxo-5H-7-thia-1,11b-diaza-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
109
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(112 citation statements)
references
References 21 publications
1
109
0
1
Order By: Relevance
“…Most importantly, CX-5461 single-agent therapy in PDX AML significantly reduced the leukemic load Figure 7I). Together, these data significantly extend the earlier study of CX-5461 in a xenografted human cell line, MV4-11 AML, 16 and provide compelling evidence of the therapeutic potential of pharmacologic inhibition of Pol I transcription in human AML, mediated in part by reducing the LIC population and suppression of the clonogenic potential.…”
Section: Org Fromsupporting
confidence: 70%
See 1 more Smart Citation
“…Most importantly, CX-5461 single-agent therapy in PDX AML significantly reduced the leukemic load Figure 7I). Together, these data significantly extend the earlier study of CX-5461 in a xenografted human cell line, MV4-11 AML, 16 and provide compelling evidence of the therapeutic potential of pharmacologic inhibition of Pol I transcription in human AML, mediated in part by reducing the LIC population and suppression of the clonogenic potential.…”
Section: Org Fromsupporting
confidence: 70%
“…To support our findings that the antileukemic effect of CX-5461 is due to on-target inhibition of Pol I transcription, 7 AML cell lines were tested for their sensitivity to 2 additional Pol I inhibitors, BMH-21 14 and low-dose ActD, 15 and an inactive compound (CX-5447), which is structurally similar to CX-5461. 7,16 Both BMH-21 and ActD decreased cell viability after 48 hours in 7 AML cell lines with the level of sensitivity broadly correlating with that of CX-5461 ( Figure 3F). As expected, CX-5447 at equivalent concentrations to efficacious doses of CX-5461 did not decrease cell viability in any of the 7 AML cell lines (supplemental Figure 4A), nor altered Pol I transcription (supplemental Figure 4B; representative cell lines SHI-1 and KG-1 shown).…”
Section: Aml Cells Are Highly Sensitive To Inhibition Of Pol I Transcmentioning
confidence: 79%
“…Ribosomal RNA is transcribed by RNA Pol I, which is not inhibited by α-Amanitin (Bensaude, 2011), and our experiments using EU (Figure 3B) do not distinguish between RNA polymerases. We therefore set out to revisit the roles of DNA replication and RNA transcription during mid-to-late zygote development using specific small molecule inhibitors added at 5 hpi: Aphidicolin, for DNA replication, α-Amanitin for RNA Pol II-mediated transcription and CX-5461 (Bywater et al, 2012; Drygin et al, 2011; Haddach et al, 2012) for RNA Pol I-mediated transcription. Of note, activity of both RNA Pol I and II has been detected indirectly in zygotes using specific promoter-driven reporter plasmids (Nothias et al, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we found that nascent 18S rRNA, assessed as above by quantification of FISH signal in the PNs, is drastically reduced in both mPN and fPN in Hira mutant embryos at 10 hpi (Figure 4C). Thus, fixation procedures that are suboptimal for studying the nucleolus (Haukenes and Kalland, 1998), lower sensitivity RNA FISH protocols and the lack of specific RNA Pol I inhibitors until recently (Bywater et al, 2012; Drygin et al, 2011; Haddach et al, 2012) may all have contributed to the idea that rRNA transcription is either absent or irrelevant in the zygote.…”
Section: Resultsmentioning
confidence: 99%
“…It is always assumed that the mechanism of action relevant to cancer is related to the well-known role of miRNA in cytoplasmic RNAi. However, cancer cells are often associated with aberrant nucleoli (46), and a Pol I inhibitor is currently in stage I trials as an anti-cancer compound (47,48). Thus, the connection between miRNA and cancer may be related to this poorly understood role in the nucleolus.…”
Section: Discussionmentioning
confidence: 99%